Pengaruh Current Ratio (CR), Return On Assets (ROA), Earning Per Share (EPS), Dan Net Profit Margin (NPM) Terhadap Harga Saham Perusahaan Real Estate And Property Yang Terdaftar Di Bursa Efek Indonesia Periode 2010-2014 - Antareka, Lena; , Imron Rosyadi, S.E., M.Si; , Lukman Hakim, S.E., M.Si (2016)
The purpose of this research is to analyze the influcences between Current Ratio (CR), Return On Assets (ROA), Earning Per Share (EPS), and Net Profit Margin (NPM) to stock price of Real Estate and Poperty company which listed in Indonesia Stock Exchange in 2010-2014 period. Data used in this research is secondary data which is financial statements collected from Indonesia Capital Market Directory (ICMD). For determining samples using purposive sampling method that is determining sample by creating some criteria. From that method there are 33 company that match with certain criteria. The amount of data of this research obtained by using pooling data method that is multiplying the amount of the company which are 33 company and the period which are 5 years, so that data are 165. Data analysis using linear regression method. Hypothesis test using t test to know the individual influence between independent variables to dependent variabel. F test used to know the simultaneous influences between Current Ratio (CR), Return On Assets (ROA), Earning Per Share (EPS), and Net Profit Margin (NPM) to stock price. Coefficient regression also used to know the ability of independent variables on determining the dependent variable. The result of this research shows that stock price is simultaneously significant influenced by Current Ratio (CR), Return On Assets (ROA), Earning Per Share (EPS), and Net Profit Margin (NPM). Only Current Ratio (CR) have no significant influence to stock price. On the other side, Return On Assets (ROA), Earning Per Share (EPS), and Net Profit Margin (NPM) individualy has the significantly influence to stock price. From the coefficient regression test known that 73,6% of stock price can be explained by independent variables.